Development of Small-Molecule Inhibitors Against Zika Virus Infection - Wang, Lili; Liang, Ruiying; Gao, Yaning; Li, Yanbai; Deng, Xiaoqian; Xiang, Rong; Zhang, Yina; Ying, Tianlei; Jiang, Shibo; Yu, Fei (Frontiers in Microbiology, 2019)
In recent years, the outbreak of infectious disease caused by Zika virus (ZIKV) has posed a major threat to global public health, calling for the development of therapeutics to treat Zika virus disease. Here we described the different stages of the ZIKV life cycle and summarized the latest progress in the development of small-molecule inhibitors against ZIKV infection. We also discuss some general strategies for the discovery of small-molecule ZIKV inhibitors.